Digital Repository in Manipal University Jaipur: A Case Study - Shivraj, K. S. (Indian Journal of Information Sources and Services, 2019)
The paper discusses the importance of Digital Repository of a University Library and provides an overview of the Digital Repository of Manipal University Jaipur. The case study of the Digital Repository of the Learning Resource Centre of Manipal University Jaipur is to illustrate the best practices indicated in the NAAC recommendation and it would be helpful to the University libraries to adopt best practices to improve Quality Services to the user community. It concludes that the establishing of Digital Repository in a University is mandatory to provide right information to the right reader in digitized form to enable the readers to excel in their academic, research and development.